Identification of a novel HEXB Mutation in an Iranian Family with suspected patient to GM2‐gangliosidoses. Issue 12 (11th August 2020) - Mansouri‐Movahed, Fatemeh; Akhoundi, Fatemeh; Nikpour, Parvaneh; Garshasbi, Masoud; Emadi‐Baygi, Modjtaba
Abstract: Sandhoff disease is one of the GM2‐gangliosidoses which is caused by a mutation in the HEXB preventing the breakdown of GM2‐ganglioside. We report a novel HEXB variant in a family with a history of a dead girl with Sandhoff disease which was not found in controls. Abstract : Sandhoff disease is one of the GM2‐gangliosidoses which is caused by a mutation in the HEXB preventing the breakdown of GM2‐ganglioside. We report a novel HEXB variant in a family with a history of a dead girl with Sandhoff disease which was not found in controls.